The Relationship of Self Efficacy and Self-Concept with Anxiety during Clinical Practice after the Covid-19 Pandemic in Students of the STIKes Santa Elisabeth Nursing Study Program Medan in 2022 - Floresta Br Sitepu; Abdul Munir; Nur'aini Nur'aini (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
The purpose of this study was to determine the relationship between self-efficacy and self-concept with anxiety during clinical practice after the Covid-19 pandemic among students of the Nursing Study Program STIKes Santa Elisabeth Medan in 2022. The research subjects were 78 students, where the sample technique used was total sampling. The research method used in this study is a quantitative method with a correlational approach. In this study, researchers used 3 (three) types of scales, namely the anxiety scale, self-efficacy scale and self-concept scale. The data analysis technique used in this research is multiple regression analysis technique. Based on the results of data analysis obtained data that: (1). There is a significant negative relationship between self-efficacy and anxiety where the coefficient value R = -0. 405 and the determinant coefficient R2 = 0.164 with a p value <0.05, meaning that the lower the self-efficacy, the higher the anxiety, and vice versa. (2). There is a significant negative relationship between self-concept and anxiety where the coefficient value R = -0.455 and the determinant coefficient R2 = 0.207 with a p value <0.05, meaning that the lower the self-concept, the higher the anxiety, and vice versa. (3). There is a significant negative relationship between self-efficacy and self-concept with anxiety where the coefficient value R = -0.527 and the determinant coefficient R2 = 0.278 with a p value <0.05, meaning that the lower the self-efficacy self-concept, the higher the anxiety, and vice versa. This means that anxiety is formed by self-efficacy and self-concept with a contribution of 27.8%. While the remaining 72,2% Anxiety is influenced by other factors such as age, education level, access to information, adaptation process, socioeconomic level (Kaplan and Sadock, 2010).